2015
DOI: 10.3171/2014.10.jns141204
|View full text |Cite
|
Sign up to set email alerts
|

Management and outcomes of pituitary apoplexy

Abstract: OBJECT This study was undertaken to analyze the predisposing factors, clinical presentation, therapeutic management, and clinical recovery in patients with pituitary apoplexy, with an emphasis on the long-term visual, endocrine, and functional outcomes. METHODS The authors performed a retrospective analysis of consecutive cases involving patients treated at Mayo Clinic between 1992 and 2013. Patients were included in the study only if they had 1) abrupt onset of severe headache or visual disturbance in the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
104
1
12

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(121 citation statements)
references
References 35 publications
4
104
1
12
Order By: Relevance
“…The middle- and long-term outcome of patients with pituitary apoplexy is strictly related to (i) the pathomechanisms of pituitary damage, (ii) the involvement of optic tract and oculomotor nerves, and (iii) the occurrence of SAH [101]. At the same time, in our opinion, a multidisciplinary management as well as a skilled and dedicated surgical team could affect the outcome of pituitary apoplexy.…”
Section: Prognosismentioning
confidence: 99%
See 1 more Smart Citation
“…The middle- and long-term outcome of patients with pituitary apoplexy is strictly related to (i) the pathomechanisms of pituitary damage, (ii) the involvement of optic tract and oculomotor nerves, and (iii) the occurrence of SAH [101]. At the same time, in our opinion, a multidisciplinary management as well as a skilled and dedicated surgical team could affect the outcome of pituitary apoplexy.…”
Section: Prognosismentioning
confidence: 99%
“…In the former condition, hypopituitarism is frequently permanent, while in the latter one recovery of endocrine function can be obtained by debulking of the pituitary mass [63, 106]. However, in terms of endocrine outcome, some studies showed that pituitary hormones deficiencies consequent to pituitary apoplexy infrequently recover and the persistence of hypopituitarism seems to be not related to management modalities [4, 96, 99, 101, 107]. …”
Section: Prognosismentioning
confidence: 99%
“…There is a 10% risk of apoplexy in incidentally discovered macroadenomas. 1 • Pituitary adenomas often show asymptomatic bleeding, which is detected during surgery, on pathology, or on magnetic resonance imaging (MRI); 14 to 25% of patients with a pituitary adenoma have asymptomatic bleeding. [2][3][4][5] Pituitary apoplexy, therefore, is a clinical and not a pathological diagnosis.…”
Section: Incidencementioning
confidence: 99%
“…If at any point during this monitoring process the patient becomes unstable or the patient's condition worsens, or if there is a deterioration in the level of consciousness, then surgery should be considered. 1,17 Outcome Death is very rare in pituitary apoplexy, and in generally is related to intraoperative complications (vascular injury) or acute secondary adrenal insufficiency. Extraocular cranial neuropathy in general resolves over time, regardless of the treatment.…”
Section: Medical Managementmentioning
confidence: 99%
“…The symptoms of pituitary adenomas, such as headache, visual function impairment, and pituitary function insufficiency, usually manifest as compression effects on the dura mater in the sella, the optic chiasm, and the pituitary gland (1)(2)(3)(4). Intratumoral hemorrhages occur frequently and can exacerbate the symptoms of the adenoma, but there are many grades of severity (5,6).…”
Section: Introductionmentioning
confidence: 99%